1996
DOI: 10.2307/328635
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Multimedia Annotations on Vocabulary Acquisition

Abstract: Research on second language (L2) vocabulary acquisition has revealed that words associated with actual objects or imagery techniques are learned more easily than those without. With multimedia applications, it is possible to provide, in addition to traditional definitions of words, different types of information, such as pictures and videos. Thus, one of the fundamental research questions posed in the use of multimedia systems is: How effective are annotations with different media types for vocabulary acquisit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
185
5
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(209 citation statements)
references
References 8 publications
(9 reference statements)
10
185
5
9
Order By: Relevance
“…Chun and Plass [15] revealed that words associated with actual objects or corresponding images are learned more easily than those without. In addition, Carpenter and Olson [16] reported that one of the most common findings in cognitive research is that image-based learning is easier for learners in long-term memory recalling.…”
Section: Copyright C 2017 the Institute Of Electronics Information Amentioning
confidence: 99%
See 1 more Smart Citation
“…Chun and Plass [15] revealed that words associated with actual objects or corresponding images are learned more easily than those without. In addition, Carpenter and Olson [16] reported that one of the most common findings in cognitive research is that image-based learning is easier for learners in long-term memory recalling.…”
Section: Copyright C 2017 the Institute Of Electronics Information Amentioning
confidence: 99%
“…This study also investigated the reasons that lie behind the ineffectiveness of vocabulary learning via text + image + audio approach, and concluded that i) learners' learning styles and ii) the speech rate of the recorded annotation were involved. Furthermore, Chun and Plass [15] investigated the effectiveness of annotations with different multimedia types while acquiring a new vocabulary. The study result with regard to the effectiveness of different types of annotations concluded with significantly higher scores for words supported by text + picture than words with text-only and video + text.…”
Section: Cavl: State Of the Artmentioning
confidence: 99%
“…However, this study is different from the previous studies mentioned because it made use of a more authentic CALL environment and examined student behavior as it occurred during student interaction with the program. Chun and Plass (1996) performed an even more authentic study in which they had 160 second year German students use an interactive multimedia CALL reading program Their first research question was to determine the degree to which learners acquired vocabulary incidentally through reading in a hypertext environment. Their study reported a 24.1%-26.5% range for the subjects' performances on post-study retention measures.…”
Section: Authentic Learning Environmentsmentioning
confidence: 99%
“…Each performed research with reading texts observing learner choices within real CALL multimedia environments and analyzing the relationship between learners' look-up behavior and learner performance. As noted by Chun and Plass (1996), the importance ofthese studies is that they include all or most of the variables that are present in real L2 learning environments.All of these studies can be classified into categories based on their interface with L2teaching (Pica, 1997 …”
mentioning
confidence: 99%
See 1 more Smart Citation